Effects of a lifestyle intervention on daytime sleepiness and cognitive function. (31st December 2021) - Hayden, Kathleen M; Spira, Adam P; St‐Onge, Marie‐Pierre; Ding, Jingzhong; Anderson, Andrea; Molina‐Henry, Doris P; Sanderlin, Ashley H; Reboussin, David M; Espeland, Mark A; Bahnson, Judy
Abstract: Background: Daytime sleepiness is common in older adults and may result from poor nighttime sleep due to sleep disordered breathing, fragmented sleep, or other sleep disorders. Daytime sleepiness may signify disruption of circadian rhythms and disorder in neural circuitry arising from neurodegenerative disease. We investigated the association between self‐reported daytime sleepiness and cognitive function in Look AHEAD, a randomized clinical trial of an intensive lifestyle intervention (ILI) in a cohort of adults with type 2 diabetes (T2D) and overweight or obesity at baseline. Method: Participants (aged 45‐76 years) were randomized to ILI or diabetes support and education (DSE) conditions. After ∼10 years, the trial was stopped; observation continued to year 18. We included participants who reported levels of daytime sleepiness at baseline and year 18 (n=2, 825). Change in daytime sleepiness was defined as increasing, stayed the same, or decreasing levels of daytime sleepiness. Cognitive assessments at years 13 and 18 included measures of global function, memory, executive function, and attention; a cognitive composite was derived from z‐score averages. The relationship between change in daytime sleepiness from baseline to year 18, and cognitive function at year 18 was examined using analysis of covariance, adjusting for year 13 cognitive performance, baseline age, gender, race/ethnicity, education, APOE ε4 carrier status, baseline CVD history, and baseline daytime sleepiness. Result: Participants who reported increased daytime sleepiness from baseline to year 18 (n=402), performed significantly worse on the cognitive composite than those who reported no change (n=1089) or decreased levels of daytime sleepiness (n=948), (Least Squares Mean [standard error]) ‐0.50 (0.04); ‐0.40 (0.03), and ‐0.39 (0.03), respectively; p ‐value=0.004. Significant interactions between treatment arm and daytime sleepiness were found in executive function ( p <0.10) and memory ( p <0.001) such that relationships were stronger among ILI compared with DSE participants including poorer scores among those with increasing daytime sleepiness in the executive function (34.3 (0.72); p <0.02); and memory domains (6.5 (0.30); p <0.05). Conclusion: Increasing daytime sleepiness over 18 years predicted poorer cognitive performance in older individuals at high risk for sleep disorders. ILI may exacerbate relationships between increasing daytime sleepiness and cognitive deficits in adults with T2D and overweight/obesity.